Respuesta :
Answer and Explanation:
Given : Consider the relationship [tex]3r+2t=18[/tex]
To find :
A. Write the relationship as a function r=f(t)
B. Evaluate f(-3)
C. Solve f(t)= 2
Solution :
A) To write the relationship as function r=f(t) we separate the r,
[tex]3r+2t=18[/tex]
Subtract 2t both side,
[tex]3r=18-2t[/tex]
Divide by 3 both side,
[tex]r=\frac{18-2t}{3}[/tex]
The function is [tex]f(t)=\frac{18-2t}{3}[/tex]
B) To evaluate f(-3) put t=-3
[tex]f(-3)=\frac{18-2(-3)}{3}[/tex]
[tex]f(-3)=\frac{18+6}{3}[/tex]
[tex]f(-3)=\frac{24}{3}[/tex]
[tex]f(-3)=8[/tex]
C) Solve for f(t)=2
[tex]\frac{18-2t}{3}=2[/tex]
[tex]18-2t=6[/tex]
[tex]2t=12[/tex]
[tex]t=\frac{12}{2}[/tex]
[tex]t=6[/tex]
The value of f(-3), to write the relationship as a function (r = f(t)) and to solve the (f(t) = 2) expression, arithmetic operations can be use. Refer the below calculation for better understanding.
Given :
3r + 2t = 18
A) 3r = 18 - 2t
[tex]r = 6-\dfrac{2t}{3}[/tex] ---- (1)
where, [tex]\rm f(t)=6-\dfrac{2t}{3}[/tex] ----- (2)
B) [tex]r = 6-\dfrac{2t}{3}[/tex]
Given that f(-3) imply that t = -3. So from equation (2) we get
f(-3) = 8
C) Given that f(t) = 2. So from equation (2) we get,
[tex]2 = 6 -\dfrac{2t}{3}[/tex]
2t = 12
t = 6
The value of f(-3), to write the relationship as a function (r = f(t)) and to solve the (f(t) = 2) expression, arithmetic operations can be use.
For more information, refer to the link given below:
https://brainly.com/question/21114745